CHANGES IN THE NUMBER OF MICROORGANISMS IN LIGHT GRAY SOILS CONTAMINATED WITH INDUSTRIAL WASTE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the results of studying changes in the number of certain soil microorganisms under the influence of industrial waste contamination of light gray soils distributed in the Guzar district of Kashkadarya region.